(untitled) (Law and world, 2024)
Rape survivors are mostly women, and the perpetrators are mostly men. So, it has a social and cultural dimension. In the article, the problems regarding rape law are shown from the angle of the female rape survivors. The paper discusses how rape is interpreted in Georgian criminal law practice and why one paradigm of rape prevails to this day - a male stranger and a fighting woman who physically resists the perpetrator. Criminal law sets the standard of the “ideal victim’’ for a woman, the “rational” rules of action during rape; in particular, it determines what the “typical behavior” is for a woman before, during, and after sexual violence. If the female rape survivor’s response does not fit into this standard, she remains outside the legal system; her voice is suppressed and disbelieved by the justice. The paper critically examines the Georgian legislative and judicial definition of rape; However, the research is not limited to this; it also includes an analysis of the approaches and scientific views of other jurisdictions. The paper supports a liberal understanding of sexual autonomy and consent. The goal of the paper is to show the essence of non-consensual sexual violence and its superiority compared to the old rape law. Keywords: Rape law, consent, yes means yes Introduction The paper aims to show the incompleteness of the composition of rape limited to physical violence that it fails to protect sexual autonomy adequately. The Georgian rape law, which enumerates methods of rape by names such as violence, threat of violence, and helplessness, their judicial interpretation is even narrower.[1] Such a non-comprehensive definition of sexual violence runs counter to the goals of liberal criminal law. And the state violates the positive obligation to protect citizens from violence.[2] This paper discusses the definitions of rape, both the Georgian rape law and the definitions of non-consensual sexual violence, by observing different countries and scholarly approaches. Georgia, as a signatory state to the Council of Europe Convention on Preventing and Combating Violence Against Women and Domestic Violence (the Istanbul Convention), must modify non-consensual rape. Today, the main discussion among scholars in Western society and academia is about how to formulate the non-consent rape law, in particular, whether consent as its main element should be considered “attitudinal” or always in the form of “communication”. A universal approach to consent has proven to be one of the most difficult issues to tackle, and this has led to many different views and perspectives surrounding it.[3] In this paper, communication theory is supported. The aim of the paper is also to outline the negative and positive aspects of sexual autonomy to draw a line between the actions that must be punished to protect the negative right to sexual autonomy and also to outline the behaviors that should not be punished to protect the positive right to sexual autonomy. The paper also discusses the mens rea of ​​rape, analyzing which is the best model for criminal law purposes, such are the approaches of England and Wales[4],[5]which involves evaluating the perception of consent from the perspective of a reasonable person, taking into account what efforts were made to ensure the consent of the other party regarding sex. Thus, under this model, a person will not be punished for a mistake in consent if the mistake is reasonable, which precludes avoiding liability simply for an ``honest mistake”. This standard leaves no space for shielding responsibility by referring to the cultural factor. However, what is considered “reasonable” can be subject to manipulation. Maximum certainty of law, consistent judicial interpretations, and scholarly interpretations are important to ensure this.[6] The goal of the paper is to show the superiority of consent-based rape law over coerced-based rape law. In addition, the task of the paper is not to propose any specific model of consent but rather to outline the superiority of more general theoretical foundations and approaches that will strengthen the position for rape law reform. As far as I understand the scope of criminal law with a liberal philosophy, I look at the regulation of sexual violence from the same perspective. My views are influenced by liberal thinkers such as J.S. Mill, H. L. A. Hart, J. Feinberg, S. Green and many other liberals. Regarding the boundaries of sexual autonomy, consent, and sexual violence, the influence of liberal feminists and scholars is also great,[7] in particular, such as M. Nussbaum, C. Paglia, K. Harding, V. Despentes, and many others. Although I did not follow the views of radical feminists in terms of the application of substantive criminal law, in particular, the extent to which sexual violence should be defined, how to define exploitation, or the voluntariness of sexual consent, I was greatly influenced by their texts. There are issues on which feminists, whether radical or liberal, agree, and these are the issues of disclosure of sexual violence and access to justice. I share their views on the discriminatory impact of gender stereotypes and rape myths on access to justice. 1. The Need to Rethink the Definition of Rape 1.1. Undarstanding of Rape Law There are different views on what should be considered sexual violence and what should be a legal interest protected from rape. One approach is patriarchal-moralistic, which is reflected with more or less intensity by a large number of jurisdictions, including liberal criminal law, especially its judicial interpretations.[8] In this approach, the boundaries of sexual violence are very narrow. Physical violence (with few exceptions), as well as the victim’s utmost resistance to the perpetrator, are the necessary actus reus of the crime. Even if the law does not explicitly emphasize the requirement to resist the aggressor, it is interpreted as such in practice. It was with the same approach that the husband was protected by immunity from raping his wife.[9] Such a reservation was never found in the Georgian legislation, but practically there were no statistics of cases of marital rape. Those women who could not fit into the existing social constructs regarding women, the standard of the “ideal woman” established by the patriarchy, were also not protected. The legal good protected by the patriarchal-moralistic approach is not the sexual autonomy of a person but some abstract entity - family honor, father’s property, and female chastity. This was the legal interest protected by medieval European criminal law.[10] These “interests” have been banished from modern liberal criminal law. In the patriarchal-moralistic approach, many actions that are inherently sexual and which are done without the will of the other party, and thus it is sexual violence, are not prohibited. It should also be noted that the moralistic approach justifies the criminalization of some sexual behaviors that are excluded from the catalog of crimes under liberal criminal law. Such is prostitution, although it is not punishable by the article prohibiting rape, but by another norm. The legal interest protected from prostitution is the institution of the family and morals. The sex worker is usually punished for this.[11] The prohibition of rape defined by the Georgian criminal law and its court interpretations is precisely moralistic-patriarchal.[12] Despite recent legislative changes, it has not fundamentally changed. Chapter 22 of the Criminal Code of Georgia (hereinafter CCG), which includes five crimes against sexual freedom and inviolability, was partially reformed under the influence of the Istanbul Convention. With the amendments of May 2017, the definition of rape became gender neutral; the legislator removed moralistic terms and differentiation into “traditional” and “non-traditional” forms of sex. According to the new definition, for a sexual act to be classified as rape, it must necessarily be penetrative in another person’s body, and penetration with any part of the body and in any form will not change the qualification of rape. However, the definition still reflects both moralism and gender specificity. In particular, as far as the emphasis in the definition is on penetration into another’s body, and such a case of rape is ignored, when the body of the victim is used to penetrate the body of the perpetrator, practically according to the formalistic definition, such cases are not assessed as rape.[13] The main problem that the Georgian rape law has is limiting it to narrow cases of violence, threats of violence, and helplessness. The need for the reform to be modified in the absence of consent to include more actions that encroach on sexual autonomy has been delayed for many years for unjustified reasons, even though more and more books and articles are being written in the Georgian academic field in support of the changes, as well as the great efforts of non-governmental organizations and feminists to make the state reform.[14] It is also true that the methods of rape - violence, threats of violence, and helplessness can be interpreted more broadly than their current understanding,[15] especially since the European Court of Human Rights (hereinafter Strasbourg Court) standard exists in this regard,[16] however, we see that the Georgian criminal law practice still views and evaluates sexual violence from a moralistic and patriarchal perspective, and this is the main obstacle to progress. The standard for defining violence as sufficient to suppress a woman’s will is very strict, while much less pressure is sufficient to overcome a woman’s resistance. The starting point of moralistic-patriarchal criminal law is not the protection of individual sexual autonomy but the determination of the self-sacrificing struggle of a woman to protect her “honor”. Female rape survivors examine with a magnifying glass how they behaved before, during, and after the rape.[17] The ideal rape victim is a dead woman or a woman who has been mutilated in a fight with the rapist to defend her “honor”. This unfairly strict standard also applies to child victims, which will be discussed later with the analysis of a specific case. The extent to which patriarchal ideology defines the boundaries of sexual violence is interesting for a systematic analysis of the law. In particular, the definition of Article 1433 of the Criminal Code, the first part of which stipulates three to five years of imprisonment as a punishment for using the services of a trafficking victim, is important for understanding the limits of the legislator’s understanding of rape. This article includes both adult and minor victims. The victim of trafficking has been deprived of free choice, which is why she is a victim of trafficking. When a person understands that the other sex participant gives consent to sex due to coercion (i.e. her consent is not genuine) and despite this, sex is initiated with her, this is rape.[18] A systematic interpretation of these and other norms reveals that the legislation supports the narrow scope of rape. Only rape committed with physical violence is considered serious enough to be considered rape, and the punishment is imprisonment for six to eight years in the case of an adult, while the same action against a minor is imprisonment for a term of fifteen to twenty years or life imprisonment. The practical interpretation of Article 139 of the Criminal Code also proves this. Establishing sexual relations with a person without her consent under the influence of the threat of disclosure of personal information is punishable by imprisonment for up to five years. Both the doctrinal and the modern Georgian court’s interpretation of this norm is such that the norm includes not only threats but also the realization of threats, that is if a frightened victim obeys the threat of the abuser and has sex with him.[19] It is interesting to discuss the case, and how Georgian criminal law will deal with it. This case of rape actually happened[20] but did not reach the justice system due to gender prejudices and rape myths against the female victim. Anna was 19 years old when she woke up to find her roommate, a 30-year-old man, “groping” her in her bed. She had no past or present romantic relationship with this man. That night, while Anna was sleeping, the man lay down next to her and then sexually penetrated Anna’s body without any communication with her. Anna, talking to the researcher, when she remembered the case, mentioned that after waking up, although everything happened very quickly, she remembered what thought came to her mind for a moment when she found a man lying next to her, it was fear, because if she tried to escape, he would still catch her and, worse might happen. Is it rape? Yes, it is. Sexual penetration of the woman’s body took place without her consent. Anna frightened and captivated by the thoughts that the worst would happen to her, simply “preferred” immobility. It is unreasonable for a 30-year-old man to expect that the woman’s silence meant that she agreed to his initiative. The woman did not consent to sex. It would not be a surprise to the perpetrator that he could frighten the woman by initiating sexual behaviour on the body while she was sleeping, especially if they were alone at home. According to Georgian criminal law, this case would not be considered rape. Because the perpetrator did not use the physical violence established by the Georgian standard, he did not make any threats, nor is it a classic case of helplessness.[21] If her body had been sexually penetrated while she was asleep, it would have been rape, but Anna woke up before the penetration, so according to the Georgian criminal code, she had to fight physically to protect her “honesty”. Rape defined as non-consensual includes all of the above, which is fair. Where sexual penetration of another person’s body takes place without the other person’s free consent - it is rape, regardless of the physical marks on the body. A Feminist Approach One of the broadest understandings of sexual violence is the feminist approach. “Broad” refers to the low threshold for violence to be considered a crime. Sexual violence is any unwanted sex, sex that takes place under any form of pressure. These include prostitution (pressure caused by social inequality), sex with the threat of separation (emotional pressure),[22] in a word, sex that takes place without the enthusiasm of the other party. A feminist understanding of sexual exploitation takes into account the general context of gender and social inequality, statistics on employment and unequal pay, as well as social constructs, and more.[23] That is why they consider sex work as a form of exploitation because, according to their assessment, it is “inherent” for prostitution to objectify a woman and dehumanize her.[24] According to this approach, the legal interest protected from sexual violence is the dignity and equality of women as a group.[25] With the same approach, pornography should be banned as a tool for the “normalization” of violence against women, as well as BDSM, which is a “romanticization” of the patriarchal order.[26] However, taking into account the general context mentioned above, they do not trust women’s consent regarding the listed sexuality, they do not consider women as autonomous decision-makers. This radical feminism approach is paternalistic, presenting a woman as childlike who needs special protection from the state.[27] Such paternalism is unacceptable to the liberal understanding of personal autonomy I discuss below. There are two common understandings of autonomy: the liberal understanding of autonomy – individual autonomy and relational autonomy. This latter approach is popular in the radical feminist texts mentioned above. Among the supporters of relational autonomy is the British scholar J. Herring too.[28] According to him, the liberal understanding of autonomy does not consider that a person is a social being and makes decisions under the influence of society. That is why he suggests that to understand autonomy, we should pay attention to the context, both special and general.[29] Jenifer Nedelsky is also a supporter of relational autonomy.[30] According to this approach, a person’s decision should not be judged in isolation from the demands of society. [31] The origin of this type of autonomy is to protect the individual from the harm of violent relationships. [32] It should be noted here that protecting an individual from a violent relationship not only does not contradict the liberal approach, but it is a strict follower of this principle. J. Herring, without naming the liberal authors, writes that they don’t seem to take into account the violent experience that precedes sex, which affects free will, which I think is an undeserved criticism of liberal scholars I know.[33] Liberals have a problem with the very broad definition of a “violent environment” for criminal law purposes, while proponents of relational autonomy explain it by accepting the general unequal social context, which is sufficient for them to exclude the voluntariness of the given consent.[34] This is not enough from a liberal point of view, it tries to maintain a balance based on the goals of criminal law and also shows caution based on the goals of protecting positive sexual autonomy.[35] J. Herring, based on this approach, advocates a “strong” form of consent, which implies freedom from all coercion for the validity of consent.[36] The liberal understanding of consent and sexual autonomy is disliked by relational autonomy advocates precisely because it does not define the voluntariness of consent so strictly.[37] That’s why many cases of what is acceptable sex for liberals are sexual assaults for relational autonomy advocates. An example of this is prostitution.[38] It’s also an unfair accusation against liberals that they seem to ignore gender stereotypes and rape myths.[39] Cultural factors and social learning affect a person in general; it is not related to liberalism.[40] A Liberal Approach As for the liberal understanding of personal autonomy, it views the individual as a rational agent and entrusts her with the right to dispose of their own life.[41] S. Green distinguishes normative and descriptive understanding of autonomy. The first is related to the right to act according to one’s desire and will.[42] The restriction of which is justified only when its realization poses a threat to another person’s right.[43] Sexual autonomy also means the right to use your sexuality as a tool for your own needs.[44] The descriptive aspect of autonomy is related to the ability of a person to manage her own life, which will be dictated by her motives, and not by exploitation.[45] Sexual autonomy has a variety of expressions, just as there are people and their individual choices and attitudes regarding sexuality. Sexual autonomy includes a person’s right to have sex with whoever they want and in whatever way they want, or not to have sex at all. Have sex by yourself, own and use a sex toy for sexual purposes, use legal pornographic material, buy or sell sex work, get involved in BDSM, have sex in a group, and more.[46] From the liberal point of view, the main thing is that all these activities take place with the participants' consent, and the expressed consent is informed and free. Liberal criminal law establishes paternalistic care only for certain groups who are incapable of making free decisions, e.g., due to their age or health condition.. 1.2. The Impact of Different Approaches on the Application of Criminal Justice Criminal law is applied to different extents, depending on whether it is understood liberally or under some other philosophy. Legal scholars list the types of relationships that are characterized by subordination and power imbalance. Sexual intercourse in this type of relationship and context attracts the attention of the law. These types of relationships include relationships between a prisoner and prison warden, a prisoner and a police officer, a student and a lecturer, a priest and a parishioner, a patient and a doctor, and many others.[47] In an absolute approach, the sexual proposal and act of the person in the vertical of power in this type of relationship is violent and should be criminalized without any contextual analysis. The contextual approach favours a differentiated approach in this relationship (concerning some parts). Liberal scholar of criminal law, S. Green, separates the relationship between the arrested and the policeman, where he allows an absolute approach. Focusing on the power of the policeman, his special training, weaponry, and ability to cause life-threatening harm to the arrested, and on the other side is the person deprived of his/her liberty, which is completely defenseless and completely under the control of the state, such an imbalance of power is considered enough to prohibit sex in such a relationship with an absolute approach. Here, Green believes that even if we imagine consensual sex in this type of relationship, an absolute ban is acceptable for him, assuming that the risk of abuse of power is very high. A flexible law would complicate investigations, increasing false negatives in the cases of accused police officers.[48] Thus, the liberal point of view is not unfamiliar to absolute approaches, depending on the context. Green advocates absolute punishment, among other things, because of the institutional issue that it is in everyone’s interest for an official who is a witness, investigator, or prosecutor to be impartial.[49] From the liberal perspective, a contextual approach is preferred in other types of relationships, such as a lecturer and an adult student relationship, social hierarchy in the workplace and so forth. To the extent that radical feminists take into account the general situation and social constructs, this is where the linear evaluations of the sexual relationship of the parties regarding sex in hierarchical social relations come from. With such an approach, there is no space left for opinions about voluntary sex. According to a liberal approach, the criminalization of sex in a workplace would be justified in the case of analysis of the specific context and detection of suppression of the will. 2. Sexual Autonomy, Consent, Voluntariness 2.1. Sexual Autonomy The legal interests protected from sexual violence are sexual autonomy and inviolability. Also, the attack on an individual’s sexual autonomy is rightly considered an insult to human dignity.[50] Chapter 22 of the Criminal Code, which includes violent acts of a sexual nature, is entitled to sexual freedom and inviolability. Sexual autonomy has two aspects, positive (the right to have sex according to one’s motives) and negative (the right not to be subjected to unwanted sexual behavior).[51] An individual’s positive right to have sex with whoever they want will always be outweighed by the other person’s negative right to be protected from unwanted sexual activity.[52] The goal of criminalizing sexual behavior is to protect a person’s negative sexual rights, but the positive rights of the same person should not be overlooked here. For example, the intersections of negative and positive aspects of sexual autonomy are best seen when legislation prohibits sexual intercourse with an individual with an intellectual disability.[53] Such an absolute approach violates the human right to have sex.[54] That is why it is always important to take into account the degree of disability, the context, and the nature of the relationship between individuals. Legal scholars, such as S. Green and T. Hörnle, in such a case they, are opposed to an absolute ban.[55] Because where there is a person’s consent, the state must respect it and not interfere in the relationship, because there is no interest to protect. 2.2. Voluntariness The liberal understanding bases the assessment of the voluntariness of participation in sexual relations on objective criteria.[56] Voluntary participation in sex means the free choice and decision of the participants. A sex-related offer that is not a freedom-restricting but a freedom-enhancing coercive offer,[57] whether or not the consent given to sex excludes the voluntariness, is considered controversial in the philosophy of law[58] and the doctrine of criminal law.[59] Feinberg gives an example of this from a millionaire’s offer to finance surgery to save her critically ill son if she has sex with him.[60] Due to the situation, Feinberg calls this proposal coercive, because a person is in a hopeless situation, if she does not agree to the proposal, her child will die. That is why Feinberg agrees with the nullification of such a contract, although he considers such consent regarding sex sufficiently voluntary for criminal law purposes and, therefore does not justify its use.[61] The millionaire has no obligation to pay her for anything. With this proposal, the chances of the child increase; if she does not agree, she will remain in the same situation as before, for which the millionaire is not responsible.[62] Taking advantage of a person’s predicament situation and offering a sex proposal excludes consent and is therefore considered sexual violence in the Georgian criminal law doctrine. One approach takes into account the age of the victim, if the manipulative proposal is not evaluated as rape about an adult, the author is in favor of paternalistic approach concerning minors.[63] This approach is compatible with the objectives of criminal law. The second approach focuses on the special intensity of the pressure, regardless of whether the offer is freedom-restricting or freedom-enhancing,[64] another view focuses on the victim’s vulnerability and need for care, and when a person manipulates this situation to achieve the desired result, even though he has no duty of care[65] A freedom enlarging offer addressed to a person in need, needs a more careful approach for criminal law purposes[66] because in such cases attention should be paid to the positive right of the offeree to sexual autonomy. As mentioned above, part of sexual autonomy is using sexuality for a need, not just for pleasure. Freedom restricting coercion affects the voluntariness and, ultimately, the validity of consent.[67] Coercion and voluntariness should be assessed precisely by analyzing the specific context according to the degree and intensity of coercion used.[68] Circumstances may exclude the validity of consent; an example of this is the case that will be discussed below. Georgian judicial practice is problematic in defining the voluntariness of consent concerning sex. There are hundreds of judgments confirming this from both old and modern times.[69] Clear evidence of this is one of the last cases from the Georgian judicial practice, which, along with other similar cases, drew the attention of the Public Defender of Georgia.[70] The judge does not take into account the violent climate in which the victim is, they look for physical injuries and other signs of hand-to-hand combat with a magnifying glass on the victim’s body to determine rape, which is an oversimplification of the rape narrative. In the case discussed below, the perpetrator was punished for sexual intercourse with a minor (the victim was 15 years old). Although the prosecutor’s office charged him with rape, the court downgraded the qualification (voluntary sexual intercourse with a person under the age of consent (art. 140).[71] According to the court, you cannot be a victim of rape if you do not have physical marks on your body, in the absence of such traces, the justice system tells the victim that she got what she wanted - “asking for it”.[72] According to the mentioned case, a 15-year-old girl was kidnapped by three adult men, one of whom wanted to marry her. The court did not question the fact of abduction and illegal deprivation of liberty,. The judge said that it would be difficult for the child to overcome the resistance of three men, but the accusation of rape was not convincing. According to the judge, sexual intercourse took place in private, where only the child and the accused were in the room; in such a situation, the child was obliged to resist physically. The judge emphasized that the child had no physical injuries on her body and her clothes were not torn.[73] The fact that the child was deprived of liberty, left alone at home, where there is no chance of help, and the perpetrator is physically stronger than her, was not enough for the judge to consider sex in such a violent environment as rape. Moreover, in such an environment, the “consent” of a person could not be valid. The judge narrowed the rape down to the presence of physical harm and its failure to find it was sufficient to establish the voluntariness of the sex. This is an oversimplification of what constitutes sexual violence and the context in which it occurred, the very primitive measure used by law enforcement agents to define abuse. In the same situation, if the victim were 16, the perpetrator would not be held criminally responsible with such an explanation. The content of sexual violence, consent, and voluntariness regarind sex are understood from a patriarchal perspective. Georgian criminal law functions with a patriarchal logic. 2.3. Consent The element of consent is not new to Georgian criminal law. Absence of consent, although not spelt out in words, is implied in the definition of rape just as it is considered in other crimes, such as illegal deprivation of liberty (Art. 143). Consent, as an objective element of rape, excludes its actus reus, as well as illegal deprivation of liberty. Concerning assault, consent is not the composition of the act but the matter of wrongfulness. According to Green’s correct remark, such a division is correct for theoretical and practical reasons.[74] Not considering non-consent as actus reus of rape would lead to the formal criminalization of any sex,[75] which is unimaginable. The principle of “not to harm” justifies criminal law. Therefore, assault is prohibited regardless of consent, and given the specific context, it may be justified. These two approaches differentiate these crimes in terms of the burden of proof. In the first case (sexual violence), the prosecutor asserts the absence of consent, and in the second case (assault), the defendant proves that the injury occurred with consent.[76] According to Article 36 of the Istanbul Convention, the definition of rape is as follows: “engaging in non-consensual vaginal, anal or oral penetration of a sexual nature of the body of another person with any bodily part or object”.[77] According to this definition, the essential objective element constituting rape is the sexual penetration of another person’s body without consent. Physical violence or threats are not a necessary element. Consent is what gives a person the right to sexually penetrate the body of the consent giver, and in case of withdrawing the consent, he is obliged to stop the sexual act. A person’s body is not accessible to others until they give their consent. In the case of consent, there is no longer any obligation to refrain from sexually touching the other person’s body, and the giver of consent will no longer have a claim unless the sexual impact on her body continues despite the refusal of permission. Thus, consent must accompany the entire process, from start to finish, or the action will turn into violence. The rape-by-violence paradigm is very common in various jurisdictions, and such an understanding is still common in countries where the definition of non-consensual rape was reformed a long time ago, notably in Germany[78] and England/Wales.[79] The deconstruction of this paradigm was initiated by international criminal tribunals in the legal assessment of sexual violence committed in war contexts.[80] This was later followed by a 2003 case of the Strasbourg Court,[81] where the Court criticized the overly simplistic narrative of rape, which does not always cover what happened, leaving sexual autonomy unprotected. The Court found the violation due to a one-dimensional investigation of rape, which is narrowed down to the physical marks on the body and does not take into account the full picture, where a lot of other evidence can reveal what happened. After the mentioned case, the Strasbourg Court issued dozens of other decisions against Romania, Moldova, Slovakia, and others and found violations of fundamental human rights on the part of the state, with the same arguments.[82] The Strasbourg court will also establish a violation in Georgia if such a lawsuit is filed, because this is a systemic problem in Georgian criminal justice, gender prejudices are ingrained in prosecutors and judges. Among the instruments of international law, the CEDAW Committee, its 2008 decision Tayag Vertido v. Philippines,[83] where the committee found a gender-biased justice system and a primitive rape paradigm as a violation of human rights. Thus, it is very clear under international human rights law that rape is a violation of a fundamental human right. Rape in several cases and contexts constitutes genocide and crimes against humanity. Also, in the presence of a relevant purpose and motive, it constitutes a composition of torture. This is one of the reasons why it is considered a Jus Cogens norm.[84] Consent Models Many countries have reformed the rape law, including several US states, Great Britain, Germany, Spain, Sweden, Denmark, Iceland, and others. Many academic texts have been written, and there are many ongoing projects in various research centers to understand the nature of consent regarding sex. There are already many understandings of consent regarding sexual penetration. Among them, “attitudinal” and “communication” theories are the most common. The first focuses on the victim’s perspective and their rights,[85] what matters is what they wanted, and what the abuser thought is irrelevant. And, for the communication theory, it is important how the abuser understood the consent of the party.[86] The main thing here is that consent is declared objectively because only after that is sexual contact allowed. If an aggressor sexually penetrates a passive person because the aim was to rape her and post factum, it turns out that the party wanted to have sex with him, this is not rape according to the “attitudinal” theory. According to the theory of communication, it should be punishable because consent regarding sex was not declared objectively.[87] One of the supporters of the attitudinal theory is the American legal scholar V. Bergelson, her main criticism of communication theory is directed at its comprehensiveness, also criticizes paternalism towards women, that women’s will to have sex does not trust the state until they actively and loudly say about it.[88] Criticism is directed at the limitation of personal autonomy because passivity is part of it and must be respected by the state.[89] Consent about sex should be the result of communication. This is the correct approach for criminal law purposes, because what a person thinks cannot be known otherwise. In general, criticism has been accumulated regarding the consent model, among which it is worth noting T. Palmer’s remarks, which defines sex as a free negotiation between parties, and describes the essence of sexual violence accordingly, is correct.[90] The author considers the “consent” model to be the cause of all the practical problems that accompany the investigation and conviction of rape, which cannot be shared. The problem is a sexist culture, and neither the definition she offers will be a panacea in such a culture. During and simultaneously with the introduction of the consent model, we should not forget that it is necessary to fight against gender stereotypes and rape myths. No Means No vs Yes Means Yes “No” Model There are two models of formulating consent: “No means No” and “Yes means Yes”. Both models have been criticized. The “no” model has been mainly criticized for its under-inclusiveness. [91] According to Green, this model looks like an old rape law because the refusal to have sex - “no” is interpreted with violence.[92] It should also be said that the “no” model, which demands activity from the victim, is not only a case of tonic immobility,[93] which modern science indicates to show the non-comprehensive nature of violence-based rape law,[94] but also cannot deal with classic cases of helplessness.[95] The “no model has been criticized for maintaining the old approach, namely placing the burden of proof on the victim to have refused sex.[96] The criticism is fair because the “no” model creates fertile ground for perpetuating the old narrative that silence is consent. The “yes” model tells the parties that before you initiate sexual behavior, you must make sure that the participant also wants it, otherwise, it is violence, and you will be punished. “Yes” model It is considered that the “Yes” model has an educational function.[97] It is a more understandable concept for criminal law[98] and does not contain a signal supporting rape, as is the case with the “no” model. The “Yes” model has also been criticized on various counts, including for being over-inclusive and for rigid guidelines in interpersonal relationships. It should be noted that the “Yes” model is also criticized for supporting the rape myth. In particular, it strengthens the myth that rape occurs due to improper communication between the parties, for which the woman is responsible.[99] The criticism is not fair. By changing the coerced-based rape law to non-consensual, the message is not that before the law was vague and people did not understand each other’s communication, but like the purpose of all new norms, the purpose of this change is to say more loudly what was previously silenced in society and became a social norm, that today is not tolerated. And it does this with a new formulation of the norm. The “yes” model is criticized in terms of establishing one standard of communication when people’s abilities are different,[100] as well as the absolute obligation of the parties to actively express their consent to sex when the participant may want to be passive.[101] In response to the criticism, it should be said that the context matters, if people tell each other what they want with signs that others may not understand, this is not a violation of the prohibition of rape understood by the “yes” model.[102] The purpose of the law is not to allow sexual exploitation, where the latter did not take place, the act will not be assessed as rape. Mens rea is also a protective mechanism against excessive criminalization. It is Green’s opinion that the “Yes” model overcomes gender stereotypes; the established idea that a woman is passive and the initiator of sex is always a man is opposed to it. This model tells sex participants if they want sex, then they should say about it.[103] Green considers the way to avoid over-inclusivity of rape law, on the one hand, to formulate actus reus with many situations[104] and to define mens rea by the standard of reasonable person.[105] When a person reasonably believes in consent, this should exclude criminal liability. It should also be said that there are a thousand forms and signs of consent regarding sex in a very close and interpersonal relationship. Therefore, in such a relationship, if the consent is disputed, mens rea will be the shield, and the person who made a mistake in understanding the consent will not be punished. Schulhofer[106] is a supporter of the communication theory and the “Yes” model, who, to overcome the criticism mentioned above that the “Yes” model leads to excessive criminalization of sex, supports the contextual model of the “Yes” model, which, taking into account the context, in particular cases excludes liability for sexual intercourse with a passive partner.[107] Unlike the “no” model, this will apply to narrower cases and the law will be based on a positive wording of consent.[108] It should be noted that the contextual understanding of consent is also supported by the Istanbul Convention. From this point of view, the Swedish model is interesting, explaining consent by communication - by word or action and in any other form. In the definition of rape, the word “consent” is not mentioned at all, and the emphasis is on the voluntariness of participation in the sexual act, which is the actus reus of rape. Consent may be expressed verbally or non-verbally and in any form. Based on the explanatory note of the law, the researchers emphasize that the Swedish model is a hybrid.[109] It is a synthesis of communication and implied consent.[110] In certain contexts, female passivity is considered sexual autonomy. For example, according to the explanatory notes of Swedish law, sexual penetration with a sleeping partner is not rape.[111] Another supporter of the theory of communication is T. Hörnle, however, taking into account the ultima ratio principle of criminal law, she supports the German “no” model.[112] The difference is that according to the “yes” model, you need active consent from the other person before starting sex, for the “no” model passivity is a sign of consent in a situation that does not suppress the will. If the person does not refuse despite the opportunity, sexual penetration will not be considered rape.[113] This model is recognized by the criminal law of Germany,[114] (as well as Switzerland[115]) where the definition of rape is formulated as initiating sex with a person despite hir clear refusal.[116] Thus, with this model, the burden of denial is shifted to the victim. T. Hörnle, in a situation that is not oppressive, sees no problem in shifting the burden of refusal onto the victim in comparison to how much punishment the other party may face.[117] I cannot say that this model is non-comprehensive and therefore bad, especially since the German penal Code defines many situations where the victim is not obliged to refuse, including cases of helplessness and intimidating circumstances.[118] Although, on a symbolic level, it evokes those old, gender stereotypes that refusal is a sign of consent, it can also blur the line between sex and rape in many situations, invoking the cultural factor.[119] Especially if the mens rea standard is as weak as in the German rape law. Therefore, the legislation formulated with the “yes” model is more acceptable. It should be noted here that the practical definition of gender crimes showed the tendencies of dishonest use of criminal law. For example, qualifying the act as provoked murder instead of evaluating it under a strict article of femicide;[120] Non-fatal strangulation of a female partner is considered assault;[121] Lightly punishing forced marriage and rape in the name of “creating a family”, etc.[122] Therefore, to completely prevent such interpretations, a strict approach to the law is desirable, if you want sex, say about it. And informing the party in advance that a woman’s body is inviolable until she gives her consent is fair. A Canadian scholar agrees to allow implied consent only in very intimate relationships and non-penetrative sexual behaviors.[123] Also, when we talk about the permission given for sex, we don’t mean only a verbalized “yes”. “Yes” can be expressed by different signs, when these signs are familiar to the partners, no problem arises. When people are strangers to each other, more effort is needed to ensure agreement. 3. In Search of a Better Model of Mens Rea Under the reformed rape laws, two main approaches to mens rea have been established. Both models are essentially the same,[124] because communication regarding sex and perception of circumstances are evaluated from the perspective of a reasonable person. Canada, some jurisdictions of the US, and England/Wales may belong to the first group, and Sweden to the second group.[125] In assessing the efforts made by the accused to ensure the risk, whether the partner consented to the sexual intercourse with him or not is tested, and how reasonable the mistake was, taking into account the circumstances in which it occurred. In the first approach, there is only one rape law and a mistake made concerning consent is evaluated under one offense. And in the case of the second approach, rape committed with intent is punished by a separate article, and its commission by negligence is a separate article. In the latter case, the punishment is light.[126] The approach implies that a person can initiate sexual activity only if he is sure of the consent of the other party. The judge/jury will look at what the defendant did to make sure the sex partner permitted him to have sex. It is not enough for the defendant to claim that he made an “honest mistake” or “thought that she agreed”, nor will his interpretations of the events become a sufficient basis for excluding responsibility.[127] Mistakes and reasonable efforts made to ensure the consent of the party are evaluated by what steps the accused took for this, and what kind of communication he had with the victim. According to Canadian rape law, as indicated by the scholars, it is not enough to prove that “honest mistake” or “I thought that her “no” actually meant “yes” and other similar voluntary manifestation of blindness, the purpose of which is to avoid responsibility.[128] As V. Munro rightly notes, the high degree of mens rea of ​​rape creates an opportunity to use the patriarchal cultural factor.[129] That is why the law should not allow a person to justify himself with simple words because of the mistake he made.[130] A person will be punished if there is no evidence in the case that the party actively and voluntarily participated in sex.[131] It should be noted that the German model sets the minimum threshold of mens rea about consent to indirect intention, whose volitional element differs from the Anglo-American recklessness.[132] The German court’s definition of indirect intention is very similar to the approach of England and Wales before 2003 when even a silly, unbelievable but “honest mistake” was enough to exclude mens rea concerning consent. It should be noted that the reform did not touch the subjective element of sexual violence in Germany. German scholar T. Hörnle is in favor of mens rea reform with sexual violence according to the Swedish model.[133] Hörnle explained this by saying that the test of evaluating factual mistakes and recklessness from the perspective of a reasonable person is generally not an established institution in German criminal law.[134] Several researchers pointed out the practical problems of the second approach. Most of the cases are classified as negligent rape, and the perpetrators are given light sentences.[135] It has become even more manipulative to distinguish between cases of intent and negligence.[136] That is why the first model deserves support. The difficulty of communicating about sex is surmountable. If you are not sure about the consent of the other party, you should not initiate sex. If a person takes a risk, then responsibility is also fair. The case of R v Ewanchuk[137] is interesting which the Supreme Court of Canada decided in 1999 and found the accused guilty. With this decision, the court followed the theory of communication of consent and took into account the test of “reasonable steps” to evaluate mens rea of sexual violence.[138] The victim, 17 years old, went to the accused for an interview. The accused offered to enter the trailer to show the woodworks (he related himself as a businessman in wood-working business). The victim left the door open, but the accused closed it, making the girl think he blocked the exit. The victim was terrified. The man started touching her, each subsequent touch was more intimate and with more intensity. The victim told him to stop several times. Then the man would stop, the girl wouldn’t make a sound at that time, and the man would continue the sexual touch. The court did not interpret the girl’s shorts and passivity in moments as her consent to sexual touch (The defense strategy is to use the rape myth to defend the accused, that the woman dressed provocatively and she invited rape - asking for it) . It is beyond all reasonableness for the accused to expect that the girl liked and wanted his touch. The Supreme Court has criticized the definition of consent with similar gender prejudices. In the given situation, the girl refused to be touched several times, and she was scared and had no control over the situation. The abuser should not initiate sexual contact without consent. A woman’s “no” means “no”, translating it into consent is the stubbornness of the abuser and nothing else. Concluding Remarks The article has shown that the composition of rape provided by Georgian criminal law is based on patriarchal-moralistic ideology, this is especially well seen during judicial interpretations of the norm, how voluntary participation in sex is defined. It is also clear that the legal design to protect an individual’s sexual autonomy is practically still evaluated through the lens of morality. Women subjected to violence are looked at by the agents of justice with a magnifying glass, they are required to remain in the construction of the “ideal victim”, otherwise the system leaves them behind. The paper supports the liberal understanding of sexual autonomy and related concepts, which, on the one hand, requires a strict approach to punish all those actions that are performed in disregard of the true will of another person and, on the other hand, to limit punishment where there is free consent to sex, to protect the individual’s positive right to sexual autonomy. In the paper, based on my observation and also on many other Georgian and foreign studies, it is clear that there is a need to change the coerced-based rape law to non-consent rape law. Among the consent models, the paper has shared consent understood through communication as the “yes means yes” model. This model will most likely create a basis for cultural myths not to be used as a shield to protect the perpetrators. The same argument supports the mens rea standard of rape, which considers only a reasonable mistake of fact to exclude liability, which is determined by observing what reasonable steps the accused took to convince the other person’s consent. Bibliography Anitha, S. & Gill, A. (2009). Coercion, Consent and the Forced Marriage Debate in the UK. Feminist Legal Studies, 17. Bibbings, L., & Nicolson, D. Feminist Perspectives on Criminal Law (eds.) Feminist Perspectives on Criminal Law, Routledge-Cavendish; Bladini, Moa & Andersson, W. S. (2020). Swedish Rape Legislation from Use of Force to Voluntariness - Critical Reflections from an Everyday Life Perspective. Bergen Journal of Criminal Law and Criminal Justice, vol. 8(2); Bow, H. & Herring, J. (2023). ‘Rough Sex’ and the Criminal Law. Emerland Publishing; Kramer Friedman, J. & Valenti, J. (2019). Yes Means Yes, Visions of Female Sexual Power and a World without Rape. Seal Press; De Heer, B. A. & Jones, L. C. (2023). ‘Tonic Immobility as a Defensive Trauma Response to Rape: Bridging Public Health and Law’ Violence Against Women. Dekanosidze, T. and Pataraia, B. (2020). Commentary on Crimes Against Sexual Freedom and Inviolability. Sapari; (Georgian) Dubber, M. D. & Hörnle, T. (2014). Sexual Autonomy, The Oxford Handbook of Criminal Law. Oxford University Press; Dworkin, R. (1997). Taking Rights Seriously. Harvard University Press; Eriksson, (2010). Defining Rape, Emerging Obligations for States under International Law? Kållered; Feinberg, J. (1986). Harm to Self. The Moral Limits of Criminal Law. Oxford University Press; Gardner, J. And Shute, S. The Wrongness of Rape, Oxford Essays in Jurisprudence. Oxford 2002; Gavey, N. (2019). JUST SEX? The Cultural Scaffolding of Rape. Routledge; Gegelia, T. (2021). The Rape Paradigm: Violent Stranger VS Warrior Victim, Journal “Law and World”, 7 (3); Gegelia, T. (2022). Non-Fatal Strangulation in the Context of Family Violence. Caucasus University Periodical Edition, Collection of Articles, vol. 2; (Georgian) Gegelia, T. (2022). Criminalization of Defensive Violence in Response to Intimate Partner’s Aggression. Bad Law or Vicious Criminal Practice? International Journal of Law: Law and World, 24(8); (Georgian) Gegelia, T. (2022). Georgian Regime of Regulation of Prostitution and its Watchdogs. Journal of Constitutional Law, Vol. 2; Gegelia, T. (2024). Female Rape Survivor in the Trial and Epistemic Injustice, Journal of Constitutional Law, N1; Gegelia, T., Kelenjeridze, I., & Jishkariani, B. (2020). Sexual Offences. World of Lawyers; (Georgian) Green, S. P. (2020). Criminalizing Sex: A Unified Liberal Theory. Oxford University Press; Harding, K. (2015). Asking for It. The Alarming Rise of Rape Culture – and What We Can Do About It. Da Capo Press; Herman, J. (1981). Father-Daughter Incest. Harvard University Press; Herman, J. (2023). Truth and Repair: How Trauma Survivors Envision Justice. Basic Books; Herring, J. (2020). Criminal Law: Text, Cases, and Materials, Oxford University Press; Hörnle, T. (2022). Sexual Assault Law Reform in a Comparative Perspective. Oxford University Press; Hörnle, T. (2024). The Challenges of Designing Sexual Assault Law. Current Legal Problems, Vol. XX; Hoven, E. & Weigend, T. (eds). Consent and Sexual Offenses, Comparative Perspectives. Nomos; Jishkariani, B. (2022). Private Part of Criminal Law. Crime Against a Person. World of Lawyers; (Georgian) Kelly, L. (1998). Surviving Sexual Violence. Polity press; Lekveishvili, M., Mamulashvili, G. and Todua, N. (2019). Private Part of Criminal Law. Book 1. Meridian; (Georgian) Lockwood Harris, K. (2018). Yes Means Yes and No Means No, but Both These Mantras Need to Go: Communication Myths in Consent Education and Anti-Rape Activism. Journal of Applied Communicatiob Researcher, vol. 46(2); Mackinnon, C. A. (2019). Butterfly Politics Changing the World for Women. Harvard University Press; Mill, J. S. (1859). On Liberty. Batoche Books Limited 2001 edition; Mill, J. S. (1869). The subjection of women. Longmans, Green, Reader, and Dyer; Möller, A., Söndergaard, H.P. & Helström, L. (2017). Tonic Immobility During Sexual Assault: A Common Reaction Predicting Post-Traumatic Stress Disorder and Severe Depression. Acta Obstetricia et Gynecologica Scandinavica; Nedelsky, J. (2012). Law’s Relations: A Relational Theory of Self, Autonomy, and Law. Oxford Academic; Nussbaum, M. (1995). Objectification. Philosophy & Public Affairs, Vol. 24(4); Nussbaum, M. (2000). Sex and Social Justice. Oxford University Press; Nussbaum, M. (2001). Women and Human Development. Cambridge University Press; Paglia, C. (2018). Free Women, Free Men: Sex, Gender, Feminism. Pantheon; Raz, J. (1988). Justifying Toleration: Conceptual and Historical Perspectives. Cambridge University Press; Reed, A. & Bohlander, M. Consent Domestic and Comparative Perspectives. Routledge; Sclater, S. D. (2009). Regulating Autonomy: Sex, Reproduction and Family. Oxford Legal Studies; Smith, (2018). Rape Trials in England and Wales Observing Justice and Rethinking Rape Myths. Palgrave Macmillan; Temkin, J. (2002). Rape and the Legal Process. Oxford University Press; Torenz, R. (2021). The Politics of Affirmative Consent: Considerations from a Gender and Sexuality Studies Perspective. German Law Journal, 2(5); Valentiner, D-S. (2021). The Human Right to Sexual Autonomy. German Law Journal, 22(5). Footnotes [1] See Gegelia, T. (2020). Commentary on Article 137 of the Criminal Code of Georgia in the book: Jishkariani, B. (ed). Sexual Offenses, World of Lawyers. [2] J. Nedelsky also agrees with this opinion, although she accuses liberalism of being gender blind when it comes to violence against children and women. See Nedelsky, J. (2012). Law’s Relations: A Relational Theory of Self, Autonomy, and Law. Oxford Academic, 200. [3] For an overview of consent models, see Green, S. P. (2020). Criminalizing Sex: A Unified Liberal Theory. Oxford University Press, 26; Also see Hörnle, T. (2024). The Challenges of Designing Sexual Assault Law. Current Legal Problems, Vol. XX, 7-9. [4] See Munro, V. (2014). Sexual Autonomy. In Dubber, M. D. & Hörnle, T. (eds). The Oxford Handbook of Criminal Law. Oxford University Press, 752. [5] For an analysis of the Canadian consent model, see Nedelsky, J. (2012). Law’s Relations: A Relational Theory of Self, Autonomy, and Law. Oxford Academic, 219-221. [6] For a critical analysis, see Lacey, N. (2000). General Principles of Criminal Law? A Feminist View. In the book: Bibbings, L., & Nicolson, D. Feminist Perspectives on Criminal Law (eds.) Feminist Perspectives on Criminal Law, Routledge-Cavendish. [7] See Gegelia, T. (2022). Georgian Regime of Regulation of Prostitution and its Watchdogs. Journal of Constitutional Law - Vol. 2, 45-59. [8] For criticism of the German model in this sense, see Hörnle, T. (2024). The Challenges of Designing Sexual Assault Law. Current Legal Problems, Vol. XX. [9] For historical analysis, see Gavey, N. (2019). JUST SEX? The Cultural Scaffolding of Rape. Routledge. Also see Temkin, J. (2002). Rape and the Legal Process. Oxford University Press. [10] See Temkin, J. (2002). Rape and the Legal Process. Oxford University Press, 57. Also see Hörnle, T. (2022). The New German Law on Sexual Assault. In Hörnle, T. (ed). Sexual Assault Law Reform in a Comparative Perspective. Oxford University Press. 141. [11] For an overview of prostitution regimes, see Gegelia, T. (2022). Georgian Regime of Regulation of Prostitution and its Watchdogs. Journal of Constitutional Law - Vol. 2, 45-59. [12] For an analysis see Gegelia, T. (2021). The Rape Paradigm: Violent Stranger VS Warrior Victim. Law and World, Vol. 7 (3), 73-97. [13] For a critical analysis of Georgian judicial practice in this regard, see (eds) Dekanosidze, T. and Pataraia, B. (2020). Commentary on Crimes Against Sexual Freedom and Inviolability. Sapari, 74-75. Cf. Jishkariani, B. (2022). Private Part of Criminal Law. Crime Against a Person. World of Lawyers, 222. [14] For an analysis of other changes in 2017 and beyond, see Gegelia, T. (2021). The Rape Paradigm: Violent Stranger VS Warrior Victim. Law and World, Vol. 7 (3), 73-97. [15] The tendency to broadly define the composition of rape has clearly appeared in modern Georgian legal literature. See Gegelia, T. (2020). Commentary on Article 137 of the Criminal Code of Georgia in the book: Jishkariani, B. (ed). Sexual Offenses. World of Lawyers; Also see (eds) Dekanosidze, T. and Pataraia, B. (2020). Commentary on Crimes Against Sexual Freedom and Inviolability, Sapari. [16] See C.R. v. The United Kingdom (Application No. 48/1994/495/577), ECtHR, Judgment of 27 October, 1995, para. 34. para 41 and 42. For the case analysis, see Eriksson, M. (2010). Defining Rape, Emerging Obligations for States under International Law? Kållered, 365, 95-98. [17] Gegelia, T. (2024). In forthcoming article: Female Rape Survivor in the Trial and Epistemic Injustice. Journal of Constitutional Law, N1. [18] For a similar assessment, see Lernestedt, C. & Kagrell, M. (2022). The Swedish Move Towards (In)Voluntariness. In Hörnle, T. (ed.). Sexual Assault Law Reform in a Comparative Perspective. Oxford University Press, 180. [19] See Comments on Article 139 in the book: (eds) Dekanosidze, T. and Pataraia, B. (2020). Commentary on Crimes Against Sexual Freedom and Inviolability. Sapari; Cf. Jishkariani, B. (2022). Private Part of Criminal Law. Crime Against a Person. World of Lawyers. [20] This case is cited in this book: Gavey, N. (2019). JUST SEX? The Cultural Scaffolding of Rape. Routledge, 167. [21] For a critical analysis of the narrow interpretation of the elements of rape See Gegelia, T. (2020). Commentary on Article 137 of the Criminal Code of Georgia in the book: Jishkariani, B. (ed). Sexual Offenses. World of Lawyers. [22] Cf. Feinberg, J. (1986). Harm to Self. The Moral Limits of Criminal Law. Oxford University Press, 209; Also see Green, S. P. (2020). Criminalizing Sex: A Unified Liberal Theory. Oxford University Press, 31. Hörnle, T. (2022). The New German Law on Sexual Assault. In Hörnle, T. (ed.). Sexual Assault Law Reform in a Comparative Perspective. Oxford University Press, 157-158. [23] For criticism, see Hörnle, T. (2024). The Challenges of Designing Sexual Assault Law. Current Legal Problems, Vol. XX, 22-23. [24] See Mackinnon, C. A. (2019). Butterfly Politics Changing the World for Women. Harvard University Press. Also see Herman, J. (2023). Truth and Repair: How Trauma Survivors Envision Justice. Basic Books; Kelly, L. (1998). Surviving Sexual Violence. Polity press; For the opposite opinion, see Nussbaum, M. (1995). Objectification, Philosophy & Public Affairs, Vol. 24(4), 249-29; Also see Gegelia, T. (2022). Georgian Regime of Regulation of Prostitution and its Watchdogs. Journal of Constitutional Law, Vol. 2, 45-59. [25] See Mackinnon, C. A. (2019). Butterfly Politics Changing the World for Women. Harvard University Press, 2019. [26] See Bow H. & Herring, J. (2023). ‘Rough Sex’ and the Criminal Law. Emerland Publishing. For the liberal view, see Kramer Bussel, R. (2019). Beyond Yes or No: Consent as Sexual Process. In Friedman, J. & Valenti, J. (eds) Yes Means Yes, Visions of Female Sexual Power and a World without Rape. Seal Press, 43-53. In the same book, see Fowles, S. M. The Fantasy of Acceptable “Non-Consent”: Why the Female Sexual Submissive Scares Us (and Why She Shouldn’t), 117-125. [27] For criticism, see Paglia, C. (2018). Free Women, Free Men: Sex, Gender, Feminism. Pantheon, 85-91. Jenkins, S. (2009). Exploitation: The Role of Law in Regulating Prostitution. In Sclater, S. D. (ed.), Regulating Autonomy: Sex, Reproduction and Family. Oxford Legal Studies. [28] See Herring, J. (2009). Relational Autonomy and Rape. In Sclater, S. D. (ed.), Regulating Autonomy: Sex, Reproduction and Family. Oxford Legal Studies. [29] Ibid., 53. [30] Nedelsky, J. (2012). Law’s Relations: A Relational Theory of Self, Autonomy, and Law. Oxford Academic, 19-21. [31] Herring, J. (2009). Relational Autonomy and Rape. In Sclater, S. D. (ed.), Regulating Autonomy: Sex, Reproduction and Family, Oxford Legal Studies, 54. [32] Ibid., 58. [33] E.g. see Feinberg, J. (1986). Harm to Self. The Moral Limits of Criminal Law. Oxford University Press; It should be noted that Feinberg’s concept of coercion is also used by feminists for a broad definition of forced marriage. See Anitha, S. & Gill, A. (2009). Coercion, Consent and the Forced Marriage Debate in the UK. Feminist Legal Studies, 17, 165–184. Also see T. Hörnle and S. Green in the book: Hörnle, T. (ed.) Sexual Assault Law Reform in a Comparative Perspective. Oxford University Press; Also see Gegelia, T. (2020). Commentary on Article 137 of the Criminal Code of Georgia in the book: Jishkariani, B. (ed). Sexual Offenses. World of Lawyers; Also see Commentary on Article 137, Jishkariani, B. (2022). Private Part of Criminal Law. Crime Against a Person, World of Lawyers. [34] Herring, J. (2009). Relational Autonomy and Rape. In Sclater, S. D. (ed.) Regulating Autonomy: Sex, Reproduction and Family. Oxford Legal Studies, 62. [35] See Jenkins, S. (2009). Exploitation: The Role of Law in Regulating Prostitution. In Shelley Day Sclater (ed.), Regulating Autonomy: Sex, Reproduction and Family, 25-27. [36] Herring, J. (2009). Relational Autonomy and Rape. In Sclater, S. D. (ed.), Regulating Autonomy: Sex, Reproduction and Family. Oxford Legal Studies, 62. For a critique of neglecting the diversity of the relationship between men and women and showing it from a narrow perspective, see Nussbaum, M. (1995). Objectification. Philosophy & Public Affairs, Vol. 24(4), 278. [37] For a critique of liberalism that it does not take the general context into account, see Munro, V. (2014). Sexual Autonomy. In Dubber, M. D. & Hörnle, T. (eds) The Oxford Handbook of Criminal Law. Oxford University Press. [38] For a liberal perspective, see Jenkins, S. (2009). Exploitation: The Role of Law in Regulating Prostitution. In Sclater S. D. (ed.) Regulating Autonomy: Sex, Reproduction and Family, 25. Cf. Mackinnon, C. A. (2019). Butterfly Politics Changing the World for Women. Harvard University Press. [39] Herring, J. (2009). Relational Autonomy and Rape. In Sclater, S. D. (ed.) Regulating Autonomy: Sex, Reproduction and Family. Oxford Legal Studies, 67. [40] I have discussed the direct negative impact of gender myths and prejudices on the judicial decision-making process in the forthcoming article: Gegelia, T. (2024). In the forthcoming article: Female Rape Survivor in the Trial and Epistemic Injustice. Journal of Constitutional Law, N1. [41] See Raz, J. (1988). Autonomy, Toleration, and the Harm Principle. In Mendus, S. Justifying Toleration: Conceptual and Historical Perspectives. Cambridge University Press, 156; Dworkin, R. (1997). Taking Rights Seriously. Harvard University Press, 272-273. [42] Green, S. P. (2020). Criminalizing Sex: A Unified Liberal Theory. Oxford University Press, 19. [43] Mill, J. S. (1859). On Liberty. Batoche Books Limited 2001 edition. [44] Jenkins, S. (2009). Exploitation: The Role of Law in Regulating Prostitution. In Sclater, S. D. (ed.) Regulating Autonomy: Sex, Reproduction and Family, 32. [45] Green, S. P. (2020). Criminalizing Sex: A Unified Liberal Theory. Oxford University Press, 19. [46] Ibid., 20. [47] For the list, see Green, S. (2022). Presuming Nonconsent to Sex in Cases of Incapacity and Abuse of Position. In Hörnle, T. (ed). Sexual Assault Law Reform in a Comparative Perspective. Oxford University Press, 84. [48] Ibid., 87. [49] Ibid., 88. [50] See Hörnle, T. (2024). The Challenges of Designing Sexual Assault Law. Current Legal Problems, Vol. XX, 4; Green, S. (2022). Presuming Nonconsent to Sex in Cases of Incapacity and Abuse of Position. In Hörnle, T. (ed). Sexual Assault Law Reform in a Comparative Perspective. Oxford University Press, 77; Gardner, J. and Shute, S. (2002). The Wrongness of Rape. Oxford Essays in Jurisprudence, Oxford, 205. [51] See Green, S. P. (2020). Criminalizing Sex: A Unified Liberal Theory. Oxford University Press, 21. [52] See Ibid., 23; Also see Hörnle, T. (2024). The Challenges of Designing Sexual Assault Law. Current Legal Problems, Vol. XX. [53] See Hörnle, T. (2024). The Challenges of Designing Sexual Assault Law. Current Legal Problems, Vol. XX, 4. [54] See Green, S. (2022). Presuming Nonconsent to Sex in Cases of Incapacity and Abuse of Position. In Hörnle, T. (ed). Sexual Assault Law Reform in a Comparative Perspective. Oxford University Press, 79. [55] See Hörnle, T. (2024). The Challenges of Designing Sexual Assault Law. Current Legal Problems, Vol. XX; Also see Green, S. (2022). Presuming Nonconsent to Sex in Cases of Incapacity and Abuse of Position. In Hörnle, T. (ed). Sexual Assault Law Reform in a Comparative Perspective. Oxford University Press. [56] See Feinberg, J. (1986). Harm to Self. The Moral Limits of Criminal Law. Oxford University Press, 211-212. Green, S. P. (2020). Criminalizing Sex: A Unified Liberal Theory. Oxford University Press, 23. [57] Feinberg, J. (1986). Harm to Self. The Moral Limits of Criminal Law. Oxford University Press, 233. [58] See Feinberg, J. (1986). Harm to Self. The Moral Limits of Criminal Law. Oxford University Press. [59] See Bakhtadze, U. (2020). In: (eds) Dekanosidze, T. and Pataraia, B. (2020). Commentary on Crimes Against Sexual Freedom and Inviolability. Sapari, 65; Jishkariani, B. (2022). Private Part of Criminal Law. Crime Against a Person, World of Lawyers, 214-215. [60] See Feinberg, J. (1986). Harm to Self. The Moral Limits of Criminal Law. Oxford University Press, 231-233. [61] Ibid., 253. [62] If a person himself creates the conditions of another person’s helpless condition and then exploits her, Feinberg agrees with the use of criminal law. See Feinberg, J. (1986). Harm to Self. The Moral Limits of Criminal Law. Oxford University Press, 263. [63] Jishkariani, B. (2020). Commentary on Article 139 in Jishkariani, B. (ed.). Sexual Offenses. World of Lawyers, 72. [64] See Bakhtadze, U. (2020). In: (eds) Dekanosidze, T. and Pataraia, B. (2020). Commentary on Crimes Against Sexual Freedom and Inviolability. Sapari, 67. [65] See Lekveishvili, M., Mamulashvili, G. and Todua, N. (2019). Private Part of Criminal Law. Book 1. Meridian, 255. [66] Feinberg, J. (1986). Harm to Self. The Moral Limits of Criminal Law. Oxford University Press, 255. [67] Ibid., 254. [68] Ibid. [69] See Decision of the Supreme Court of Georgia N 2K-207 Ap.-04; Also the judgment of the Sighnaghi District Court, November 26, 2014, N 1/67-14. See also Public Defender’s Special Report. (2021). Implementation of Justice for the Crime of Child Sexual Abuse and Sexual Exploitation, 21-23. See also 2022 Report: Harmful Practice of Early/Childhood Marriage in Georgia - Current Challenges and Solutions, 32-33. [70] Public Defender’s Special Report. (2022). Harmful Practice of Early/Childhood Marriage in Georgia - Current Challenges and Solutions. [71] Decision of the Bolnisi District Court, Criminal Affairs Panel, 22 April 2021, N1/322-20. [72] For an analysis of rape myths, see Harding, K., (2015). Asking for It. The Alarming Rise of Rape Culture – and What We Can Do About It, Da Capo Press. [73] Decision of the Bolnisi District Court, Criminal Affairs Panel, 22 April 2021, N1/322-20. Par. 3.83-3.94. [74] See Green, S. P. (2020). Criminalizing Sex: A Unified Liberal Theory. Oxford University Press, 34-35. For differentiating the effect of the element of consent with respect to different crimes, see also Weigend, T. (2022). Consent and Sexual Offenses Germany. In Hoven E. & Weigend, T. (eds). Consent and Sexual Offenses, Comparative Perspectives. Nomos, 186. [75] See Green, S. P. (2020). Criminalizing Sex: A Unified Liberal Theory. Oxford University Press, 34-35. [76] Ibid., 34. [77] Council of Europe Convention on Preventing and Combating Violence Against Women and Domestic Violence (CETS No. 210), Art. 36. Available in the following link <https://rm.coe.int/168008482e>. [78] See Hörnle, T. (2024). The Challenges of Designing Sexual Assault Law. Current Legal Problems, Vol. XX. [79] See Smith, O. (2018). Rape Trials in England and Wales Observing Justice and Rethinking Rape Myths. Palgrave Macmillan. [80] E.g. see Prosecutor v. Dragoljub Kunarac, Appeal Judgement, 12 June 2002; Katanga Judgment. Prosecutor v. Germain Katanga, No.: ICC-01/04-01/07, 7 March 2014; Prosecutor v. Dominic Ongwen (2021), ICC-02/04-01/15. [81] M. C. v. Bulgaria (Application no. 39272/98) 04/03/2004. [82] See I. G. v. Moldova (Application no. 53519/07), 15.03. 2012; Y. v. Slovenia (Application no. 41107/10), 28.08.2015; I. C. v. Romania (Application no. 36934/08), 24.08.2016; C. A. S. and C. S. v. Romania – 26692/05 30.03. 2012; M. G. C. v. Romania (appl. 61495), 11. 15. 03. 2016; E. B. v. Romania (appl. 49089/10), 19.03.2019. [83] Tayag Vertido v. Philippines, CEDAW/C/46/D/18/2008. [84] Eriksson, M. (2010). Defining Rape, Emerging Obligations for States under International Law? Kållered. [85] Vera Bergelson supports this theory. See Sex and Sensibility. The Meaning of Sexual Consent. In Hörnle, T. (ed). Sexual Assault Law Reform in a Comparative Perspective. Oxford University Press, 36. [86] Supporters of this theory are: T. Hörnle and S. Green. See Hörnle, T. (ed). Sexual Assault Law Reform in a Comparative Perspective. Oxford University Press. [87] See Green, S. P. (2020). Criminalizing Sex: A Unified Liberal Theory. Oxford University Press, 26. [88] Bergelson, V. (2022). Sex and Sensibility. The Meaning of Sexual Consent. In Hörnle, T. (ed). Sexual Assault Law Reform in a Comparative Perspective. Oxford University Press, 41. [89] Ibid. [90] Plamer, T. (2017). Distinguishing sex from sexual violation: Consent, Negotiation and Freedom to Negotiate. In Reed, A. & Bohlander, M., Consent Domestic and Comparative Perspectives. Routledge. [91] Green, S. P. (2020). Criminalizing Sex: A Unified Liberal Theory. Oxford University Press, 80. [92] Ibid. [93] Green agrees with this opinion. See Green, S. P. (2020). Criminalizing Sex: A Unified Liberal Theory. Oxford University Press, 81. [94] See Möller, A., Söndergaard, H. P. & Helström, L. (2017). Tonic Immobility During Sexual Assault: A Common Reaction Predicting Post-Traumatic Stress Disorder and Severe Depression. Acta Obstetricia et Gynecologica Scandinavica; de Heer, B. A. & Jones, L. C. (2023). ‘Tonic Immobility as a Defensive Trauma Response to Rape: Bridging Public Health and Law’. Violence Against Women. [95] Cf. Green, S. P. (2020). Criminalizing Sex: A Unified Liberal Theory. Oxford University Press, 81. [96] Torenz, R. (2021). The Politics of Affirmative Consent: Considerations from a Gender and Sexuality Studies Perspective. German Law Journal, 2(5), 724. [97] Criticism of the “yes” model was also expressed from the point of view that it does not actually change the culture because it revives heteronormative concepts of gender and sexuality. See Torenz, R. (2021). The Politics of Affirmative Consent: Considerations from a Gender and Sexuality Studies Perspective. German Law Journal, 2(5), 719, 721, 725. [98] Valentiner, D-S. (2021). The Human Right to Sexual Autonomy. German Law Journal, 22(5):703-717. [99] Torenz, R. (2021). The Politics of Affirmative Consent: Considerations from a Gender and Sexuality Studies Perspective. German Law Journal, 2(5), 721; Lockwood Harris, K. (2018). Yes Means Yes and No Means No, but Both These Mantras Need to Go: Communication Myths in Consent Education and Anti-Rape Activism. Journal of Applied Communication Researcher, vol. 46(2), 159. [100] Lockwood Harris, K. (2018). Yes Means Yes and No Means No, but Both These Mantras Need to Go: Communication Myths in Consent Education and Anti-Rape Activism. Journal of Applied Communication Researcher, vol. 46(2), 170. [101] Bergelson, V. (2022). Sex and Sensibility. The Meaning of Sexual Consent. In Hörnle, T. (ed). Sexual Assault Law Reform in a Comparative Perspective. Oxford University Press. [102] Schulhofer, S. J. (2022). What Does ‘Consent’ Mean? In Hörnle, T. (ed). Sexual Assault Law Reform in a Comparative Perspective. Oxford University Press. [103] Green, S. (2022). Presuming Nonconsent to Sex in Cases of Incapacity and Abuse of Position. In Hörnle, T. (ed). Sexual Assault Law Reform in a Comparative Perspective. Oxford University Press, 87. Nedelsky also shares this opinion and agrees with the theory of communication. See Nedelsky, J. (2012). Law’s Relations: A Relational Theory of Self, Autonomy, and Law. Oxford Academic, 224. [104] Green, S. (2022). Presuming Nonconsent to Sex in Cases of Incapacity and Abuse of Position. In Hörnle, T. (ed). Sexual Assault Law Reform in a Comparative Perspective. Oxford University Press, 75. [105] Ibid., 98. [106] Schulhofer, S. J. (2022). What Does ‘Consent’ Mean? In Hörnle, T. (ed). Sexual Assault Law Reform in a Comparative Perspective. Oxford University Press, 63. [107] Ibid. [108] The Canadian model is also based on the theory of communication. For analysis, see Thorburn, M. (2022). Sexual Assault Law in Canada In Hörnle, T. (ed). Sexual Assault Law Reform in a Comparative Perspective. Oxford University Press, 100. [109] See Bladini, Moa & Andersson, W. S. (2020). Swedish Rape Legislation from use of Force to Voluntariness - Critical Reflections from an Everyday Life Perspective. Bergen Journal of Criminal Law and Criminal Justice, vol. 8(2). [110] For an analysis of the Swedish model, see Lernestedt, C. & Kagrell, M. (2022). The Swedish Move Towards (In)Voluntariness. In Hörnle, T. (ed.). Sexual Assault Law Reform in a Comparative Perspective. Oxford University Press, 174-175. Cf. Hörnle, T. (2024). The Challenges of Designing Sexual Assault Law. Current Legal Problems, Vol. XX, 9. T. Hörnle does not consider the Swedish approach as a “yes” model. She calls it the Circumstances model. [111] For criticism, see Bladini, Moa & Andersson, W. S. (2020). Swedish Rape Legislation from use of Force to Voluntariness - Critical Reflections from an Everyday Life Perspective. Bergen Journal of Criminal Law and Criminal Justice, vol. 8(2). [112] See Hörnle, T. (2022). The New German Law on Sexual Assault in Hörnle, T. (ed). Sexual Assault Law Reform in a Comparative Perspective. Oxford University Press, 146. [113] Weigend, T. (2022). Consent and Sexual Offenses Germany. In Hoven E. & Weigend, T. (eds). Consent and Sexual Offenses, Comparative Perspectives. Nomos, 189-90. [114] The extent to which the refusal was obvious is tested from the perspective of an objective observer familiar with the relevant facts. Weigend, T. (2022). Consent and Sexual Offenses Germany. In Hoven E. & Weigend, T. (eds). Consent and Sexual Offenses, Comparative Perspectives. Nomos, 190. [115] For an analysis of the Swiss “no” model, see Scheidegger, N. (2022). Switzerland. In Hoven E. & Weigend, T. (eds). Consent and Sexual Offenses, Comparative Perspectives. Nomos, 271. [116] For an explanation of paragraph 177 of the German Criminal Code, see Weigend, T. (2022). Consent and Sexual Offenses Germany. In Hoven E. & Weigend, T. (eds). Consent and Sexual Offenses, Comparative Perspectives,.Nomos. [117] Hörnle, T. (2024). The Challenges of Designing Sexual Assault Law. Current Legal Problems, Vol. XX. [118] See Weigend, T. (2022). Consent and Sexual Offenses Germany. In Hoven E. & Weigend, T. (eds). Consent and Sexual Offenses, Comparative Perspectives. Nomos, 185-186. [119] For a similar idea, see Schulhofer, S. J. (2022). What Does ‘Consent’ Mean? In Hörnle, T. (ed). Sexual Assault Law Reform in a Comparative Perspective. Oxford University Press, 65-66. Also see Bladini, Moa & Andersson, W. S. (2020). Swedish Rape Legislation from use of Force to Voluntariness - Critical Reflections from an Everyday Life Perspective. Bergen Journal of Criminal Law and Criminal Justice, vol. 8(2), 122. [120] For a critical analysis of Georgian judicial practice, see Gegelia, T. (2021). Murder Provoked by Adultery. Caucasus University Periodical Edition, Collection of Articles, vol. 1. [121] For a critical analysis of judicial practice on the example of Georgian and other jurisdictions, see Gegelia, T. (2022). Non-Fatal Strangulation in the Context of Family Violence. Caucasus University Periodical Edition, Collection of Articles, vol. 2. [122] Also see Gegelia, T. (2022). Criminalization of Defensive Violence in Response to Intimate Partner’s Aggression. Bad Law or Vicious Criminal Practice? Journal Law and World, N24, Issue 8. [123] Thorburn, M. (2022). Sexual Assault Law in Canada In Hörnle, T. (ed). Sexual Assault Law Reform in a Comparative Perspective. Oxford University Press, 100-101. [124] See Green, S. P. (2020). Criminalizing Sex: A Unified Liberal Theory. Oxford University Press, 97; Also see Herring, J. (2020). Criminal Law: Text, Cases, and Materials, Oxford University Press, 505-509. [125] For an analysis of the Swedish model, see Lernestedt, C. & Kagrell, M. (2022). The Swedish Move Towards (In)Voluntariness in Hörnle, T. (ed). Sexual Assault Law Reform in a Comparative Perspective. Oxford University Press. [126] E.g. see Wegerstad, L. (2022) Negligent Rape Law. In Hoven E. & Weigend, T. (eds). Consent and Sexual Offenses, Comparative Perspectives, Nomos, 125-126. [127] For an analysis of the Canadian model, see Thorburn, M. (2022). Sexual Assault Law in Canada In Hörnle, T. (ed). Sexual Assault Law Reform in a Comparative Perspective. Oxford University Press, 103-105; Also see Nedelsky, J. (2012). Law's Relations: A Relational Theory of Self, Autonomy, and Law, Oxford Academic, 219-221. [128] Ibid. 103. [129] Munro, V. (2014). Sexual Autonomy. In Dubber, M. D. & Hörnle, T. (eds). The Oxford Handbook of Criminal Law. Oxford University Press, 752. [130] Ibid., 752. [131] Ibid., 752. Also see Thorburn, M. (2022). Sexual Assault Law in Canada In Hörnle, T. (ed). Sexual Assault Law Reform in a Comparative Perspective. Oxford University Press, 103. [132] See Hörnle, T. (2022). The New German Law on Sexual Assault in Hörnle, T. (ed). Sexual Assault Law Reform in a Comparative Perspective. Oxford University Press, 149. [133] Ibid. [134] Ibid. [135] Wegerstad, L. (2022). Negligent Rape Law. In Hoven E. & Weigend, T. (eds). Consent and Sexual Offenses, Comparative Perspectives. Nomos, 125-126. [136] Ibid. [137] R. v. Ewanchuk (1999) 1 SCR 330 The case is cited and analyzed in the article: Thorburn, M. (2022). Sexual Assault Law in Canada In Hörnle, T. (ed). Sexual Assault Law Reform in a Comparative Perspective. Oxford University Press. [138] Ibid., 104.